The role of environmental impact assessment in addressing marine environmental issues arising from oil and gas activities: examples from Malaysia - Mustafa, Maizatun (s.n, 2012)
Malaysia being a maritime nation is well endowed with valuable resources found within her marine waters, notably that of oil and gas. These conventional sources of energy, which are being actively exploited, contribute significantly to the nation’s economic growth and industrialization. However, in the context of marine protection, oil and gas activities have the potential for a variety of adverse environmental impacts. As a developing country, the challenge here is how to balance the conflicting needs for economic development and environmental protection. Resolving this issue means finding a strategy that can take into consideration the importance of both needs. For this reason, Malaysia adopts a strategy known as the environmental impact assessment (EIA) enforced as a mandatory legislative requirement on selected activities including that of oil and gas. This paper seeks to explore the role of EIA in addressing the marine impacts from oil and gas activities. This paper argues a strong case for the application of EIA in a developing country like Malaysia as a preventive approach against environmental impact with the aim of striking a balance between development and the conservation of the environment